Effects of ride comfort on different non-driving related activities in fully automated driving experience - Mohd Norzam, Muhammad Nur Aliff; Karjanto, Juffrizal; Md. Yusof, Nidzamuddin; Hassan, Muhammad Zahir; Zulkifli, Abd Fathul Hakim; Mohd Jawi, Zulhaidi; Ab. Rashid, Ahmad Azad; Abu Kassim, Khairil Anwar (2024)
A fully automated vehicle (AV) is projected to free users from driving activities. However, motion sickness (MS) is expected to be experienced by the users when engaging in Non-Driving Activities (NDRAs) such as reading, and watching a video because they will be exposed to low-frequency movement that contributes to the development of motion sickness. This study analyzed the difference in users’ ride comfort when traveling in an AV in a real-road situation. The Wizard of Oz method was implemented for the participants to experience fully automated driving. The study was divided into three stages: pre-, during, and post-driven, to measure the user’s comfort, safety, likeness, and motion sickness level through self-report questionnaires. Three conditions of NDRA consisting of baseline (doing nothing), reading, and watching a video were tested among the young participants (18 to 28 years old, Mean = 21.4, Standard Deviation = 2.84). Statistical analysis showed a statistically significant difference between the three different NDRAs. Reading imposed the highest experienced MS followed by watching a video and doing nothing. Understanding ride comfort in AV riding is vital in designing an AV that makes the passenger enjoy the ride without any discomfort feeling (motion sickness), especially when engaging in any NDRAs